Anti-Laicism, Anti-Communism and Criticism to Freemasonry in the Salvadorian Catholic Press during the return to the debate on the Laicism of the State (1938-1940) - Chanta Martínez, René Antonio (2018)
Although the 19th century debate on the laicism has been a recurrent in El Salvador, far from being over in the 20th century, it was intensely fought when its 1939 Constitution was being forged. Based on this, this article’s objective is to present an analysis of a series of  anti-secular and anti-communist texts, found in catholic newspapers like Criterio and Chaparrastique. Three situations are interesting to note in these texts: A) The hard criticism exerted towards masonry in the anti- secular discourse; B) The strong emphasis given by catholic groups to the international context to make reference to governments that were making changes in favor of Catholicism; C) The hope of the catholic groups to revert the laicism of the State through a new Constitution of the Republic that would give the Catholic Church more rights and benefits.